Novel and lightweight digital signature scheme - WANG Hou-zhen1; ZHANG Huan-guo1 (Tongxin xuebao)
Digital signatures have many applications in information security,including authentication,data integrity and non-repudiation.However,the number theoretic-based schemes such as RSA and ECC are relatively slow in performance.These schemes do not seem to be suitable for small computing devices with limited computing capacity,such as smart cards,wireless sensor networks,and active RFID tags.Based on the hash authentication technology,a novel lightweight digital signature scheme was proposed for achieving secure and efficient signature function.Security analysis and experimental results show that it can be used as a possible alternative to the current public key cryptosystems.